2017
DOI: 10.1093/intimm/dxx032
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of immunoglobulin variable regions is supported by GANP during AID-induced somatic hypermutation in germinal center B cells

Abstract: GANP maintains antibody structural integrity during SHM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Indeed, it has been reported that this "mutation-hot" region is also a hotbed for DNA breaks leading to genomic translocations, frequently fusing BCL6 with the Ig heavy chain genes (20,47). In addition to chromatin conformation, AID access to nuclear DNA and AID-induced C > T mutations are also regulated by proteins such as GANP, which facilitates translocation of AID from the cytoplasm into the nucleus and targets it to sites of SHM (48).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that this "mutation-hot" region is also a hotbed for DNA breaks leading to genomic translocations, frequently fusing BCL6 with the Ig heavy chain genes (20,47). In addition to chromatin conformation, AID access to nuclear DNA and AID-induced C > T mutations are also regulated by proteins such as GANP, which facilitates translocation of AID from the cytoplasm into the nucleus and targets it to sites of SHM (48).…”
Section: Discussionmentioning
confidence: 99%
“…While the order of AID and Pol η mutagenesis during SHM varies slightly from that during aSHM, it is evident that a balance of these two mutagenic activities is required for fine-tuning antibody diversity. This argument is further supported by the finding that GANP (germinal center-associated nuclear protein) plays a critical role in modulating AID and error-prone polymerase activities in germinal center B-cells to facilitate the production of high-affinity antibodies (44). The cold region is devoid of H3K27ac, suggesting that the nucleosome is in a closed conformation and lacks regulatory function.…”
Section: Discussionmentioning
confidence: 92%
“…We then selected for further analysis 6 hits present in the different clusters that were not already known to regulate Dazl: BEND3, MCM3AP, KDM5C, KMT2D, SPOP, and ZBTB14 (Figure 3A-C, S3A). Among the 3 members of TREX-2 mRNA export complex, we chose to pursue MCM3AP since it is a scaffolding protein, important for the stability of the complex (Wickramasinghe et al, 2014) and it is also known to have additional nuclear functions (Eid et al, 2017;Evangelista et al, 2018).…”
Section: Screen Validation Rules Out Differentiation Artifacts and Global Effects On Known Dazl Regulatorsmentioning
confidence: 99%